SEBUAH KAJIAN PADA UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK (UU ITE) - Wahyu Agus Winarno (Universitas Jember, 2011)
Information technology gets essential role in trade and national economic growth to render social welfare. It in harmony with aim both of base and intent UU ITE which is “developing commerce and national economics in order to increase people welfare” But, in UU ITE that stills a lot of thing that need especially been added TI's exploit suitability in transactions electronics. There is a few things most overlooks that actually more have is focused deep UU ITE, for example spamming problem, well for email spammingand also personal data sell problem by banking, insurance, virus, worm computer (still implicit at Section 33) specifically for development and its broadcast, and type phising as typo pirates that makes not enjoy electronic commerce process. Keyword: UU ITE, e-commerce, information technology